Desenvolvimento de um coletor Fresnel para sistema de climatização dessecante. - Claudino Filho, Vicente de Vasconcelos (2016)
Brazil has as a main source for production of electricity the dams using water to drive the turbines and as a secondary source are used the thermoelectric power plants that use fuel oil for electric power production. Both generate a large environmental impact, due to the fact of the dams need huge areas for its construction, which often leads to destruction of important ecosystems in the region where it will be installed the hydroelectric plant, besides the fact that they need the rainfall cycle so that the dams have the operating capacity, while the thermoelectric power plants burn fossil fuels thus increasing emissions of CO2 to the atmosphere. An alternative to the solution of the problems mentioned above is the use of renewable sources of energy, with emphasis on this work. Solar energy can be divided into two parts: thermal and photovoltaic. This work it is focused on thermal use of solar energy, with a Fresnel-type solar concentrator to heat water, which will trigger a cooling system environment with the use of desiccant rotors. The choice of type Fresnel collector gave the field of development of this hub is still in constant growth and by the fact that even occupy a relatively small area when compared to other solar thermal concentrators, in addition to its construction be simple and low cost when again compared to other solar concentrators.